Pengaruh neraca transaksi berjalan, transaksi modal dan utang luar negeri terhadap cadangan devisa Indonesia - Tiara Erwina; Haryadi Haryadi; Candra Mustika (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2018)
This study aims to analyze: 1) developments in foreign exchange reserves, current account balance, capital transaction and foreign debt; 2) the influence of the current account balance, capital transactions and foreign debt on Indonesia's foreign exchange reserves. The data used is secondary data in the form of time series. The results of the study found that: 1) the average development of Indonesia's foreign exchange reserves during the period 1998-2016 was 31.60 percent per year, the current account balance was -28 percent per year, the capital account balance was 46 percent per year and foreign debt was 6.07 percent experienced a surplus from year to year but there was a deficit over the past five years; 2) Simultaneously, the current account balance, capital transactions and foreign debt have a significant effect on Indonesia's foreign exchange reserves. However, only partially, the capital account balance and foreign debt have a significant effect on Indonesia's foreign exchange reserves.